Macroeconomic Shocks and Foreign Bank Assets - Claudia M. Buch; Kai Carstensen; Andrea Schertler (Kiel Institute for World Economics (IfW), 2005)
Changes in foreign asset holdings are one channel through which agents adjust to macroeconomic shocks. In this paper, we test whether foreign bank assets change as a result of domestic and foreign macroeconomic shocks. We frame our empirical analysis in a standard new open economy macro model in which financial markets are imperfectly integrated. We test the implications of this model using dynamic panel models for changes in foreign bank assets. We find evidence that nominal interest rate differentials and inflation differentials drive changes in foreign bank assets permanently, while growth rate differentials and exchange rates have only a temporary effect.
Keywords: F3; F41; 330; international banking; macroeconomic shocks; Internationale Bank; Bilanzstrukturmanagement; Konjunktur; Schock; Zinsdifferenz; Kaufkraftparität; Neue Makroökonomik offener Volkswirtschaften; Schätzung; Schätzung; Welt